PENINGKATAN KOMPETENSI GURU DALAM PENGGUNAAN MEDIA PEMBELAJARAN MELALUI SUPERVISI AKADEMIK: SD NEGERI GADINGSARI 1 PAKEM BONDOWOSO - IMAM HANAFI (Mitra Pendidikan, 2022)
This school action research aims to 1) improve teacher pedagogical competence in the use of instructional media through academic supervision 2). Knowing what steps are taken in carrying out academic supervision in order to improve teacher pedagogical competence in the use of instructional media. This researcher used a qualitative approach because in taking action on research subjects, what was prioritized was expressing meaning; namely the meaning and process of learning as an effort to increase motivation, enthusiasm and learning achievement through actions taken (Wahid Murni et al. 2008). The type of research used was school action research (PTS). PTS is an effort to improve the performance of the education system, and develop school management to be more productive, effective and efficient This school action research was carried out at SD Negeri Gadingsari 1 Jl. Gadingsari Rt. 01 Rw 01 Pakem District, Bondowoso Regency. This research was conducted for 3 months, from January 2019 to March 2019. The research subjects were all teachers of Gadingsari 1 Public Elementary School, Pakem District, Bondowoso Regency with a total of 10 teachers consisting of 7 PNS teachers and 3 temporary teachers. This school action research was carried out at SD Negeri Gadingsari 1 Jl. Gadingsari Rt. 01 Rw 01 Pakem District, Bondowoso Regency. This research was conducted for 3 months, from January 2019 to March 2019. The research subjects were all teachers of Gadingsari 1 Public Elementary School, Pakem District, Bondowoso Regency with a total of 10 teachers consisting of 7 PNS teachers and 3 temporary teachers. This school action research was carried out at SD Negeri Gadingsari 1 Jl. Gadingsari Rt. 01 Rw 01 Pakem District, Bondowoso Regency. This research was conducted for 3 months, from January 2019 to March 2019. The research subjects were all teachers of Gadingsari 1 Public Elementary School, Pakem District, Bondowoso Regency with a total of 10 teachers consisting of 7 PNS teachers and 3 temporary teachers